THE NEED FOR ESP IN TOURISM ENGLISH IN INDIA - Dias, Naveen A. H (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Hutchinson & Waters, Swales, Selinker and Tarone, are identified as the most prominent pioneers of ESP. Hutchinson and Waters consider ESP to be a revolution in linguistics. Traditional linguists focused on the features of language, but the modern revolutionary pioneers in linguistics began to focus on the ways in which language is used in real situations. Communicative Language differs in different situations; therefore, ESP courses must be tailored to our specific needs and specific contexts so that the learners benefit further and acquire what they need than just learn General English (20).